Benumof and Hagberg's airway management - Benumof, Jonathan; Hagberg, Carin A (Elsevier/Saunders, 2013)
Enhance your airway management skills and overcome clinical challenges with Benumof and Hagberg's Airway Management, 3rd Edition. Trusted by anesthesiologists, residents, and nurse anesthetists, this one-of-a-kind anesthesiology reference offers expert, full-color guidance on pre- and post-intubation techniques and protocols, from equipment selection through management of complications. Practice with confidence by consulting the only reference exclusively dedicated to airway management, and trusted by anesthesiologists, residents, and nurse anesthetists for up-to-date information on every aspect of the field. Focus on the most essential and practical information with a concise, how-to approach, carefully chosen illustrations, and case examples and analysis throughout.